1992
DOI: 10.1007/bf02284958
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temazepam and ethanol on human psychomotor performance

Abstract: We have studied the effects of temazepam, alone and in combination with ethanol, on psychomotor performance in six healthy men and women using a battery of five microcomputer-based tasks before and 30, 90, and 150 min after treatment. The tests were pursuit tracking, divided attention, two four-choice reaction time tests and tapping rate. The entire battery required 25 min. The subjects also reported their mood at each testing time using a computerized bipolar mood scales test. Temazepam (15 mg) plus ethanol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Alcohol can compound the hangover effects of some sleeping tablets and is likely to disturb complex skills more than simpler motor tasks performed on the morning of the next day (Kunsman et al, 1992). Attention and reaction time tasks were impaired by concentrations of temazepam and ethanol in combinations that alone did not cause decrements in performance.…”
Section: Alcohol and Sports Accidentsmentioning
confidence: 99%
“…Alcohol can compound the hangover effects of some sleeping tablets and is likely to disturb complex skills more than simpler motor tasks performed on the morning of the next day (Kunsman et al, 1992). Attention and reaction time tasks were impaired by concentrations of temazepam and ethanol in combinations that alone did not cause decrements in performance.…”
Section: Alcohol and Sports Accidentsmentioning
confidence: 99%
“…Studies that have investigated their combined use offer inconsistent findings, with some studies suggesting an additive ( Roehrs, 2001 ; van Steveninck et al, 1993 ) or possibly synergistic effect ( Kunsman et al, 1992 ; Linnoila and Mattila, 1973 ; Mørland et al, 1974 ) when used in combination while others have found no such interaction ( Bond et al, 1992 ; Landauer et al, 1974 ; Linnoila et al, 1990 ; Seppälä et al, 1982 ; Taeuber et al, 1979 ). Given that as many as 88% of benzodiazepine users report the additional consumption of alcohol, and 28% indicate intentional combined use ( Ilomäki et al, 2013 ), there is an urgent need for a more comprehensive understanding of the combined effects on cognitive functioning.…”
Section: Introductionmentioning
confidence: 99%